Solving of mathematical problems as preimage of creation and developing of scientific theories - Rudalevičienė, Regina; Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2012)
In the paper some aspects of natural analogy and similarity between problem solving and creation and developing of scientific theories are discussed.